2016
DOI: 10.1097/md.0000000000005638
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an early home-based cardiac rehabilitation program for patients after acute myocardial infarction

Abstract: Background:The effect of an early short-term home-based cardiac rehabilitation (CR) program on ventricular function in acute myocardial infarction (AMI) patients is not yet clear. The purpose of this study was to evaluate the efficacy of our CR program on the improvement of myocardial function using three-dimensional speckle tracking echocardiography (3D-STE) in AMI patients.Methods:Fifty-two AMI patients were randomly assigned to 2 groups after discharge: the rehabilitation group, which participated in an ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
1
24
0
4
Order By: Relevance
“…TTE parameters, representing cardiac systolic (eg, LVEF, TAPSE) and diastolic (eg, E/A ratio, E/E’) functions are used as secondary outcomes of this trial due to the previous findings of the influence of exercise training on cardiac function 40. There is no definite information on the specific mechanisms of the influence of exercise training on cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…TTE parameters, representing cardiac systolic (eg, LVEF, TAPSE) and diastolic (eg, E/A ratio, E/E’) functions are used as secondary outcomes of this trial due to the previous findings of the influence of exercise training on cardiac function 40. There is no definite information on the specific mechanisms of the influence of exercise training on cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…27 Also in concordance with the present study, a recent study showed that early HBCR in post MI patients was associated with significant improvements in LVEF as well as global longitudinal strain, global radial strain and global circumferential strain (using 3-dimensional speckle tracking echocardiography) as compared to the control group at the 4-week follow-up. 36…”
Section: Effect Of Hbcr On LV Systolic Functionmentioning
confidence: 99%
“…Dyslipidemia, high blood pressure, obesity, diabetes, smoking, psychosocial stress, less fruit and vegetable intake, alcohol consumption, and less physical activity are the main risk factors for myocardial infarction in Chinese men and women 2 . Therefore, efforts, for example, as early revascularization therapies and secondary prevention are made to improve the quality of life of patients after acute myocardial infarction 3 but outcomes of these efforts are not satisfactory 4 and do not have large impact on success of cure of patients 5 . Cardiac rehabilitation is an outpatient model of secondary prevention and is designed to reduce the burdens of cardiovascular diseases 6 .…”
Section: Introductionmentioning
confidence: 99%